Mental disorders common among nursing residents: an analysis based on the Self-Reporting Questionnaire [Transtornos mentais comuns em residentes de enfermagem: uma análise a partir do Self Reporting Questionnaire] [Trastornos mentales comunes en residentes de enfermería: un análisis a partir del Self Reporting Questionnaire] - Camila Biscacio Falco; Janaina Mengal Gomes Fabri; Elias Barbosa Oliveira; Alexandre Vicente Silva; Magda Guimarães de Araújo Faria; Célia Caldeira Fonseca Kestenberg (Universidade Estadual do Rio de Janeiro, 2019)
Objective: to detect suspected common mental disorders (CMDs) in nursing residents, and identify related predictive factors. Method: this cross-sectional study examined a sample of 130 residents at a Rio de Janeiro city university hospital who answered the Self Reporting Questionnaire (SRQ-20) and sociodemographic questions, in 2018. The resulting data were analyzed using descriptive statistics. The study was approved by the research ethics committee. Results: the results revealed suspected CMDs in 52% of the sample, which was mainly young, single and female. Of the frequent predictors, 87.53% said they felt nervous, tense and worried, 60.7% felt tired all the time, and 57.7% slept poorly. Conclusion: the level of suspected CMDs in the sample was well above those found in studies of professionals of the health and related fields, and the predictors revealed psychological distress and risk of evolution to severe psychiatric conditions. RESUMO Objetivos: verificar a suspeição de transtornos mentais comuns (TMC) em residentes de enfermagem e analisar os fatores preditores. Método: estudo transversal com uma amostra de 130 residentes de um hospital universitário, situado no município do Rio de Janeiro, que responderam ao Self Reporting Questionnaire (SRQ-20) e questões sociodemográficas, em 2018. Os dados foram analisados por meio da estatística descritiva. Estudo aprovado por Comitê de Ética em Pesquisa. Resultados: a amostra foi composta, em sua maioria, por jovens, solteiros e do sexo feminino, cuja suspeição de transtornos mentais comuns atingiu 52%. Dos fatores preditores mais frequentes, 87,53% afirmaram sentirem-se nervosos, tensos e preocupados, 60,7%, cansados o tempo todo e 57,7% dormem mal. Conclusão: a suspeição de TMC na amostra encontra-se bem acima de estudos realizados com profissionais da saúde e áreas afins, cujos fatores preditores evidenciam sofrimento psíquico e risco de evolução para quadros psiquiátricos severos. RESUMEN Objetivo: verificar la sospecha de trastornos mentales comunes (TMC) en residentes de enfermería y analizar los factores predictores. Método: estudio transversal con una muestra de 130 residentes de un hospital universitario, situado en el municipio de Río de Janeiro, que contestaron al Self Reporting Questionnaire (SRQ-20) y cuestiones sociodemográficas, en 2018. Los datos fueron analizados por medio de la estadística descriptiva. El estudio fue aprobado por el Comité de Ética en Investigación. Resultados: la muestra estaba compuesta, en su mayoría, por jóvenes, solteros y del sexo femenino, siendo que del 52% se sospechaba trastornos mentales comunes. En cuanto a los factores predictores más frecuentes, un 87,53% afirmó sentirse nervioso, tenso y preocupado, el 60,7% sentirse cansado todo el tiempo y el 57,7% dormir mal. Conclusión: la sospecha de TMC en la muestra está muy por encima de los estudios realizados junto a profesionales de la salud y áreas relacionadas cuyos predictores evidencian sufrimiento psicológico y riesgo de evolución hacia cuadros psiquiátricos severos.